Environmental management practices within the supply chain: a case study of textile industry - Pimenta, H. C. D.; Ball, Peter D.; Aguiar, J. A.; Evans, Stephen (TU Berlin, 2013)
This study analysed the environmental management practices of a textile supply chain responsible for yarn manufacturing, located in Brazil. Using literature as the start point, a questionnaire was developed and applied with key individuals of the company. The results indicated the implementation of environmental tools, such as an environmental management system and the control of environmental aspects of the company, capable of contributing to the improvement of the company's environmental performance. It was also apparent that the environmental practices in the company studied were required for its suppliers, indicating a continuation of the environmental dimension along the supply chain. The relationship between the company and its partners indicates the existence of collaboration based on the joint development of technical and technological innovations and contribution to the improvement of training of employees.
Keywords: Environmental management practices; Green supply chain management; Textile industry